Trends in quality living and adolescent safety challenges in Nigerian (2013)
Any community large or small, urban or rural has social dimensions that will affect the health status of its adolescents. Such dimension includes fundamental changes in the political, social and economic structure of such community or society. These have changed many entrenched cultures, values and beliefs, engendering feelings of personal insecurity among Nigerians and most especially adolescent. These changes have been additionally fuelled by an increase in adolescent population, the proliferation of varying forms of personal lifestyle and domestic arrangement, and the growing dominance of unexamined subjectivity in response to moral issues. All sections and age groups of the Nigerian society are likely to be affected by safety hazards but perhaps the most vulnerable are adolescents because of society's increasing emphasis on instrumental values to the detriment of expressive ones. This article looked at the increasing vulnerability of adolescents and established the safety challenges' that adolescents encounter. It also highlighted the need for adolescents to have easy access to safety education and it should be accorded a high priority in school and educational policy.